Metasynthesis of youth suicidal behaviours: perspectives of youth, parents, and health care professionals. - Jonathan Lachal; Massimiliano Orri; Jordan Sibeoni; Marie Rose Moro; Anne Revah-Levy (PLoS ONE, 2015)
Background Youth suicide is a major public health issue throughout the world. Numerous theoretical models have been proposed to improve our understanding of suicidal behaviours, but medical science has struggled to integrate all the complex aspects of this question. The aim of this review is to synthesise the views of suicidal adolescents and young adults, their parents, and their healthcare professionals on the topics of suicidal behaviour and management of those who have attempted suicide, in order to propose new pathways of care, closer to the issues and expectations of each group. Methods and findings This systematic review of qualitative studies--Medline, PsycInfo, Embase, CINAHL, and SSCI from 1990 to 2014--concerning suicide attempts by young people used thematic synthesis to develop categories inductively from the themes identified in the studies. The synthesis included 44 studies from 16 countries: 31 interviewed the youth, 7 their parents, and 6 the healthcare professionals. The results are organised around three superordinate themes: the individual experience, that is, the individual burden and suffering related to suicide attempts in all three groups; the relational experience, which describes the importance of relationships with others at all stages of the process of suicidal behaviour; and the social and cultural experience, or how the group and society accept or reject young people in distress and their families and how that affects the suicidal process and its management. Conclusion The violence of the message of a suicidal act and the fears associated with death lead to incomprehension and interfere with the capacity for empathy of both family members and professionals. The issue in treatment is to be able to witness this violence so that the patient feels understood and heard, and thus to limit recurrences.